Kastrering av frisk tik - Ullgren, Erika; Österberg, Jenny (SLU/Dept. of Animal Environment and Health (until 231231), 2010)
In this work we have compiled results from various studies concerning medical conditions that may possibly be avoided by castration and the effects that may occur after castration of the healthy bitch. The work is a literature review but it also includes a summary on the age recommendations for castration of the healthy bitch, castration before or after the first heat and the castration method most commonly used of ovariohysterectomy and ovariectomy. The summary is based on a questionnaire answered by personnel from 20 veterinary clinics and animal hospitals evenly distributed throughout Sweden. The summary showed that ovariohysterectomy was the most common method of castration and the recommendation in age ranged from 6-12 months. Regarding castration before or after the first heat 75% of the veterinary clinics and animal hospitals answered that they recommended castration after the first heat. Literature study shows that there are both advantages and disadvantages of castration of the healthy bitch and that it therefore is important that each bitch get a personal and individual evaluation before a decision is taken concerning a castration.